Surround inhibition can instantly be modulated by changing the attentional focus - Yves-Alain Kuhn (Nature Portfolio, 2018)
Abstract To further investigate the mechanism of surround inhibition (SI) and to determine whether adopting different attentional strategies might have an impact on the modulation of SI, the effects of adopting an external (EF) or internal focus of attention (IF) on SI and motor performance were investigated. While performing an index flexion with either an EF or IF, transcranial magnetic stimulation was applied at various time points in 14 healthy subjects. When adopting an EF compared to an IF, the results show an improved motor performance (+14.7% in MVC) and a reduced bEMG in the adjacent APB (−22.3%) during maximal index flexion. This was accompanied by an increased SI in the APB with an EF (+26.4%). Additionally, the decrease in bEMG correlated with the magnitude of SI in APB. The current results demonstrate an efficient way to modulate SI by changing the attentional focus in healthy subjects and might, at least in part, explain the better motor performance being associated with an EF. The present findings help to better understand the positive mechanisms of an EF on SI in the healthy motor system and may also points towards a treatment strategy in pathologies with disturbed SI such as focal hand dystonia.